"We Wanted a Forever Family": Altruistic, Individualistic, and Motivated Reasoning Motivations for Adoption Among LGBTQ Individuals. (December 2018) - Costa, Pedro Alexandre; Tasker, Fiona
The purpose of this study was to explore motivations for adoption among a diverse sample of LGBTQ adoptive parents and prospective adopters ( n = 366) who were recruited through a U.K. network of LGBTQ adoptive and foster families to complete an online survey. Quantitative analysis showed that the majority did not think that being LGBTQ would negatively influence their experience of adopting, although they were evenly split regarding the expectation of whether they would be matched with a harder-to-place child. To explore LGBTQ parents' motivations for adoption, a thematic analysis of the qualitative data was conducted. One overarching theme was identified as seeking permanency, together with three often closely related subthemes: altruistic/moral motivation, individualistic/intrinsic motivation, and motivated reasoning. The findings reflect important changes in U.K. law since the Adoption and Children Act in 2002 permitted same-gender couples to adopt. We suggest ways to inform the recruitment of potential LGBTQ adoptive parents.